ANALISIS FAKTOR-FAKTOR KETIDAKAKURATAN KODEFIKASI EXTERNAL CAUSE PADA DOKUMEN REKAM MEDIS RAWAT INAP PASIEN BPJS DI RUMAH SAKIT ISLAM AISYIYAH MALANG - Zein, Eiska Rohmania (Politeknik Kesehatan Kemenkes Malang, 2025)
Hospitals must ensure accurate medical records to support BPJS claims. External cause coding classifies causes ofinjuries or illnesses, yet inaccuracies remain. These errors affect claims, data analysis, and service quality. At Aisyiyah Islamic Hospital Malang, 75% of external cause codes were inaccurate. This study investigates the factors contributingto these inaccuracies. This research method will use mixed methods that combine quantitative methods for percentageinaccuracy and qualitative to obtain a comprehensive understanding of the inaccuracy factors of external causecodification in the medical record documents of BPJS patients at Aisyiyah Islamic Hospital Malang. It is known from 53data that 11 medical files or 21% of the data have accurate external cause diagnosis codification, and 42 medical record files or 79% of the data have inaccurate external cause diagnosis codification. There are still many injuries diagnosed by inpatient BPJS patients at RSI Aisyiyah Malang that are not written by officers, especially in the writing of the activistcode and its classification. The factors that cause inaccuracy of external cause codification in the medical record documents of BPJS patients at RSI Aisyiyah Malang consist of 5M, namely man, machine, method, material, and money. The main factor that causes inaccuracies is the lack of complete chronological documentation from the patient, the patient or family is incomplete, making it difficult for the officer to choose the appropriate external cause code. In addition, the lack of ongoing training related to ICD-10 also contributes to errors.